Engajamento do cooperado, desafios do capital social no contexto de uma cooperativa de saúde: um estudo de caso - Bandeira, Luciana Nascimento (Universidade do Vale do Rio dos Sinos, 2020)
In a constantly changing and evolving market, the world was surprised by an unprecedented pandemic in history. Therefore, required a quick adaptation to a new way of working and a new way of providing medical assistance to the Brazilian population. In this context, medical cooperatives needed to adapt promptly so to maintain the quality of the care provided, as well as to guarantee the generation of medical work for members. In this final paper, the influence of cooperative social capital on the adhesion of cooperative doctors to the Telemedicine Project is discussed. Thus, an exploratory research was developed along with cooperative doctors from Cooperativa Alfa, whom were asked about their identification with the cooperative and their awareness of the importance of the telemedicine platform at a time when Covid-19 was increasing in the country, as well as the opportunity for a new product in addition to the assistance cost reduction, ensuring business sustainability. As a result, the opportunity to develop practices to foster cooperative social capital with members was identified, throughout their time as an associate, aside from reflections on the importance of exposing these actions to all stakeholders involved. On balance, was suggested the endless offer to join the telemedicine platform, raising awareness of the strategic importance of this product.
Keywords: Pandemia; Telemedicina; Capital social cooperativista; Pandemic; Telemedicine; Cooperative social capital